Angka Nol sebagai Kontribusi Muslim terhadap Matematika Modern - M. Kharis Majid (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
Historical development of science in the West cannot be separated from the great ‎contribution of Muslim scientists. No exception in the field of mathematics, al-Khawarizmi, ‎for example, played a major role in the development of modern mathematics. It is precisely ‎able to be seen from the work of al-Khawarizmi such as science of al-Jabar in the book al-‎Jabr wal Muqa>balah. From Khawarizmi’s work, Mathematics becomes easier to utilize in ‎trade, mapping and distributing inheritance. Besides, al-Khawarizmi's contribution in ‎Mathematics is also found in Trigonometry and the discovery of zero as a number. ‎Furthermore, al-Khawarizmi described them in a more perfect way than previous period ‎of mathematics development. Al-Khawarizmi is known developed modern mathematics ‎today, and there are still many Muslim scientists who also contributed to an advancement ‎of modern mathematic such as, Ummar al-Khayyam, al-Hajjaj, Nashiruddin al-Thusi, Ibnu ‎Haitsam and others.‎